Sex Life and Vitality During Treatment for Prostate Cancer: It Is Possible! A Case Report - Silva, Ivan Mumic; Naccarato, Angela Maria Elizabeth Piccolotto; Paz, Lucas do Prado; Fregonesi, Adriano; Ferruccio, Aline Akel; Barbuio, Maria Eduarda Bueno de Souza; França, Paloma Maria Ribeiro Lescura; Ferreira, Ubirajara; Matheus, Wagner Eduardo (Brazilian Journal of Case Reports, 2026)
Life expectancy and survival rates for prostate cancer (PCa) are improving but maintaining quality of life (QoL) during and after treatment remains a major clinical challenge. Erectile dysfunction (ED), psychosocial distress, and disturbances in body image and masculinity are highly prevalent in this population. A 66-year-old man with high-risk PCa (PSA 28.8 ng/mL; Gleason 4+5; pT3b pN1) underwent laparoscopic radical prostatectomy, adjuvant radiotherapy, and intermittent hormone therapy, presenting with ED unresponsive to oral phosphodiesterase-5 inhibitors. Health-related QoL (HRQoL) and erectile function were prospectively assessed using FACT-P (version 4) and IIEF-5. The patient attended weekly group psychotherapy from June 2022 and progressed to intracavernous injection therapy (alprostadil + papaverine + phentolamine). IIEF-5 scores improved from 5 (severe ED) to 25 (normal erectile function). FACT-P demonstrated sustained gains in emotional well-being and global QoL. A coordinated multidisciplinary pathway combining intracavernous injection therapy and continuous group psychotherapy enabled recovery of normal erectile function, sexual satisfaction, and overall well-being despite multimodal oncologic treatment.